2016
DOI: 10.1080/09286586.2016.1247876
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Trachoma in Southern Nations, Nationalities, and Peoples’ Region, Ethiopia: Results of 40 Population-Based Prevalence Surveys Carried Out with the Global Trachoma Mapping Project

Abstract: Purpose: We sought to estimate the prevalence of trachoma at sufficiently fine resolution to allow elimination interventions to begin, where required, in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) of Ethiopia. Methods: We carried out cross-sectional population-based surveys in 14 rural zones. A 2-stage cluster randomized sampling technique was used. A total of 40 evaluation units (EUs) covering 110 districts (“woredas”) were surveyed from February 2013 to May 2014 as part of the Global Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 12 publications
6
45
5
Order By: Relevance
“…We found that younger children had lower odds of TF. This finding contrasts with that of many other studies, 19,21,26,27 where the burden of TF is typically found in pre-school childrenthe age group shown to harbor the bulk of the ocular C. trachomatis reservoir in environments in which this has been studied in detail. 28,29 A shift of the burden of TF to higher age groups has been noted in areas where trachoma has lower overall prevalence, presumably because intensity of transmission (and age of first exposure) is lower in these areas.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…We found that younger children had lower odds of TF. This finding contrasts with that of many other studies, 19,21,26,27 where the burden of TF is typically found in pre-school childrenthe age group shown to harbor the bulk of the ocular C. trachomatis reservoir in environments in which this has been studied in detail. 28,29 A shift of the burden of TF to higher age groups has been noted in areas where trachoma has lower overall prevalence, presumably because intensity of transmission (and age of first exposure) is lower in these areas.…”
Section: Discussioncontrasting
confidence: 94%
“…The exception to this is the trichiasis prevalence estimate for Ma'rib, which we have not reported here because (due to the fact that an unexpectedly large proportion of adults were working outside the governorate) only 25 adults were examined in the EU as a whole. In the remainder, relatively low prevalences of TF (compared to those recorded in many parts of Ethiopia, [19][20][21] for example) were matched by low prevalences of trichiasis. Only eight EUs had TF prevalences in 1-9-year-olds ≥5%, and only five had trichiasis prevalence in ≥15-year-olds ≥0.2%, indicating a need for public health-level action.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Active trachoma was five times more likely to happen among children from 1 to 4 years old than children 5 to 9. This finding is in line with the findings of the study conducted in Ankober and southern nations and nationalities people (SNNP) [24,28]. This may be due to young children may not able to care about themselves and play in dirty places than older children.…”
Section: Discussionsupporting
confidence: 90%
“…16 In the global context, the TF prevalences recorded here are high, particularly when compared to the WHO 5% TF elimination threshold, but they are noticeably lower than TF prevalences in adjacent areas of SNNPR 19 and Oromia. 20 TF prevalences above 10% mandate full implementation of the A, F and E components of the SAFE strategy.…”
Section: Discussionmentioning
confidence: 63%